2005
DOI: 10.1183/09031936.05.00067604
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin and C-reactive protein levels in HIV-positive subjects with tuberculosis and pneumonia

Abstract: Pulmonary tuberculosis (PTB) and pneumococcal community-acquired pneumonia (PCAP) are common causes of lower respiratory tract infections in HIV-seropositive patients and may have similar clinical and radiological features. This study aimed to assess the value of serum procalcitonin (PCT) and C-reactive protein (CRP) levels in HIV-seropositive patients with pneumonia, and to investigate their potential role in differentiating pneumococcal from mycobacterial infections.HIV-seropositive patients admitted with pn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
2
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 24 publications
6
42
2
4
Order By: Relevance
“…In patients with ESR less than 100, acquired pneumonia have significantly higher CRP levels than those with pulmonary tuberculosis despite similar clinical and radiological appearances. 92 Chaudhary et al 93 reported that symptomatic mild inflammatory disease or HIV infection commonly increases CRP concentration mildly and CRP was negatively correlated with CD4 counts in HIV positive patients.…”
Section: Esr/crpmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with ESR less than 100, acquired pneumonia have significantly higher CRP levels than those with pulmonary tuberculosis despite similar clinical and radiological appearances. 92 Chaudhary et al 93 reported that symptomatic mild inflammatory disease or HIV infection commonly increases CRP concentration mildly and CRP was negatively correlated with CD4 counts in HIV positive patients.…”
Section: Esr/crpmentioning
confidence: 99%
“…Specimens were divided into two parts; one for 92 histological and the other for microbiological examinations. Due to the logistical constraints we were unable to retrieve the microbiological results back.…”
Section: Limitationsmentioning
confidence: 99%
“…Ugajin M et al (2011) studied PCT level in pulmonary tuberculosis patients and Pneumonia patients he also reported significant difference in PCT level in the two group (mean PCT in PTB group was 210 ± 490 pg/ml and in Pneumonia group was 4100 ± 8680 pg/ml) [7]. In a study by G.K. Schleicher et al on Pneumococcal pneumonia and pulmonary tuberculosis in HIV positive patients mean PCT level was 1030 pg/ml and 19050 pg/ml in the two group, respectively, with P value of <0.0005 [8].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly thrombocytopenia (count of less than 100,000 x10 9 /l) appears to signify severe disease that necessitates aggressive treatment including admission to the intensive care unit 118 . Measurement of the CRP has not been documented to be able to discriminate between PcP and BP 119 , however, using the cut off value of 3ng/ml for procalcitonin and 246 mg/l for CRP one group of investigators reported an increased capability to distinguish BP from TB with a sensitivity of 81.8% and a specificity of 82.5% for the procalcitonin and 78.8% and 82.3% respectively for the CRP 120 . In hospitalized patients the measurement of blood urea, creatinine, sugar, albumin, bilirubin, AST and ALT helps to place patients in specific risk groups for poor outcomes using the CURB -65 121 and or Pneumonia Severity Index criteria 122 The microbiological diagnosis of CABP is dependent on the detection of the pathogen itself in culture, components of the pathogen (antigen) in body fluids or the antibody response to the pathogen.…”
Section: Laboratory Testsmentioning
confidence: 99%